2023
DOI: 10.1039/d2ea00164k
|View full text |Cite
|
Sign up to set email alerts
|

A computer-based solution to the oxidation kinetics of fluorinated and oxygenated volatile organic compounds

Abstract: The OH radical is the most powerful atmospheric oxidant, being responsible for the chemical breakdown of many pollutants released into the troposphere, including saturated volatile organic compounds (VOCs). Numerous of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 105 publications
3
20
0
Order By: Relevance
“…Although the CTSR procedure does not guarantee that the lowest energy TS is found, it has shown to be a considerable improvement [22,23,31] to the oversimplified method that was used in previous versions of the MC‐TST protocol: [16,17] the twelve MC‐TST/CTSR rate constants that we have so far calculated have been compared with experimental results, agreeing with the recommended experimental rate coefficient [22,23,31] within a factor of two.…”
Section: Methodssupporting
confidence: 63%
See 4 more Smart Citations
“…Although the CTSR procedure does not guarantee that the lowest energy TS is found, it has shown to be a considerable improvement [22,23,31] to the oversimplified method that was used in previous versions of the MC‐TST protocol: [16,17] the twelve MC‐TST/CTSR rate constants that we have so far calculated have been compared with experimental results, agreeing with the recommended experimental rate coefficient [22,23,31] within a factor of two.…”
Section: Methodssupporting
confidence: 63%
“…(2) and (3) is the total rate constant for the reaction between C x F 2 x +1 CH 2 CHO and ⋅OH. Previous work concerning the CF 3 CH 2 CHO+⋅OH reaction ( x=1 ${x=1}$ ) has shown that the branching ratios calculated by structure‐activity relationships (SAR) [15,32] and by our own MC‐TST/CTSR protocol [31] yielded identical results: ΓCH2= ${{\rm{\Gamma }}_{{\rm{CH}}_{\rm{2}} } = }$ 0 % and ΓCHO= ${{\rm{\Gamma }}_{{\rm{CHO}}} = }$ 100 %.…”
Section: Theory and Computational Methodsmentioning
confidence: 81%
See 3 more Smart Citations